Introduction of cultural potential in supporting local tourism growth in the southwest sumba region through web-based information media - Mesri Welhelmina Nisriani Manafe; Hefri Yodiansyah; Ito Turyadi; Kraugusteeliana Kraugusteeliana; Eva Solina Gultom (Institute of Computer Science (IOCS), 2023)
Tourism in East Nusa Tenggara's Southwest Sumba Regency has many natural and cultural attractions, but promotion hasn’t been optimized. This study proposes the use of web-based information media to introduce and promote tourism in Southwest Sumba Regency and support the expansion of regional capacity. The objective of this study is to develop a website-based tourism information system that provides information on destinations, attractions, supporting facilities, and travel routes and can aid travelers in locating their desired destination. The implications of the research are demonstrated by the features of the system that can adapt to user requirement, and the development of information systems can assist travelers and local governments in promoting the tourism potential and regional culture of Southwest Sumba. The contribution of the research is intended to be a medium of information for tourist attractions and the cultural potential of the Southwest Sumba region, facilitating tourists' ability to locate information about tourist attractions and introducing the potential of other tourist attractions. The cultural and tourism potential information system has seven outstanding system features that can help manage tourism potential data, and the system testing results show that all system features have been implemented and are valid.